Analisis Strategi Penyelesaian Piutang Pajak Bumi dan Bangunan Perdesaan dan Perkotaan (PBB-P2) (Studi Kasus pada Badan Pendapatan Daerah Kota Tangerang) Tahun 2019-2022 - Ambarwati, Ambarwati; Futri, Silviana (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
One of the regional revenues comes from the tax sector, namely the rural and Urban Land and Building Tax (PBB-P2). However, there are still many taxpayers who do not pay and pay off their tax debts. Because of the low number of taxpayers to obey and obey in their tax obligations that lead to high amounts of receivables in the Tangerang City Regional Revenue Agency. Therefore, the purpose of this study to analyze the settlement strategy of rural and Urban Land and building tax receivables, obstacles faced and efforts made by the Tangerang City Regional Revenue Agency. This study uses a descriptive qualitative approach. The results of this study indicate that it is not fully optimal in the implementation of the settlement of PBB-P2 receivables based on the program implemented by the Tangerang City Regional Revenue Agency based on four indicators, namely organizational strategy, program, supporting resources, and institutional. Obstacles that occur is the lack of knowledge in sending system by taxpayers, double tax object numbers, and lack of bailiffs in settling receivables. Efforts have been made namely the renewal of system synchronization, open counters services in all sub-districts, put up banners and billboards, video visualization of services, conduct billing cooperation with the State Prosecutor's Office.